Student Character Development Model of Environmental Care Halal Tourism in East Lombok - Syukria, Wilda (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of this research analyzes the factors forming of environmental care students the character in the halal tourism at East Lombok Regency. This research includes qualitative descriptive using Analytical Hierarchy Process (AHP) approach (Saaty, 2008). The data collection technique used purposive sampling and Analytical Hierarchy Process (AHP) through observation, interview, questionnaire (questionnaire) and literature study. The research informants were teachers, students, and principals of East Lombok. Data analysis technique was done by data reduction, data presentation, and conclusion. The result of research of factor forming the character of the students of environmental care in the halal tourism area in East Lombok 1) “Ulama / Tuan Guru” has a very high position for the order of life in East Lombok Regency. They were become the role model of life example given in accordance with syariat Islam and pay attention to the environment. 2) Parents are the environment that shapes the character of the child so that it can be applied in the life of society. 3) Teachers can develop positive characters in students through extracurricular activities as well as foster a sense of environmental care. 4) The government has an important role in disseminating to the public about halal tourism but the community retains the existing character in people's lives without changing the existing order. 5) The community is the person who is involved in the activities that exist in the life that consider the environmental conditions to remain beautiful and far from the word dirty to be an example of the community of a region with one community in other areas, especially in East Lombok Regency.